2018
DOI: 10.1101/459396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

White Matter Microstructure Correlates of General and Specific Second-Order Factors of Psychopathology

Abstract: Increasing data indicate that prevalent forms of psychopathology can be organized into secondorder dimensions based on their correlations, including a general factor of psychopathology that explains the common variance among all disorders and specific second-order externalizing and internalizing factors. Despite this organization, and high levels of comorbidity between diagnoses, most existing studies on the neural correlates of psychopathology employ case-control designs that treat diagnoses as independent ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 72 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Replications of some findings have al­ready been published, including associations between the general factor of psychopathology and atypical white matter development 67‐69 , atypicalities in the cerebellum and its connections 70‐72 , and lack of typical segregation between the default mode and executive networks during rest 73 . Thus, we may not be far from an understanding of at least some of the neurobiological mechanisms related to the general factor of psychopathology.…”
Section: Nature Of General and Specific Factors Defined In Bifactor Mmentioning
confidence: 85%
“…Replications of some findings have al­ready been published, including associations between the general factor of psychopathology and atypical white matter development 67‐69 , atypicalities in the cerebellum and its connections 70‐72 , and lack of typical segregation between the default mode and executive networks during rest 73 . Thus, we may not be far from an understanding of at least some of the neurobiological mechanisms related to the general factor of psychopathology.…”
Section: Nature Of General and Specific Factors Defined In Bifactor Mmentioning
confidence: 85%
“…In terms of white matter integrity, commonly indexed using diffusion imaging metrics, reduced integrity in callosal (Riem et al, ) and pontine‐cerebellar (Romer et al, ) pathways are also linked to the expression of a p ‐factor. However, positive associations with corpus callosum integrity have also been observed (Hinton et al, ), hinting that neurodiversity rather than a simple deficit accompanies variation in p . Varied findings are also reported in studies of resting‐state functional connectivity, with a general psychopathology factor relating to reduced fronto‐temporal connectivity (Alnæs et al, ) as well as delayed maturation of the default mode network (DMN) (Sato et al, ), but also with increased connectivity of visual cortex with the DMN and frontoparietal networks (Elliott, Romer, Knodt, & Hariri, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the inclusion of unresolved loss or trauma as covariate in Riem et al (2019) is an important distinction from other studies, in light of substantial evidence that childhood adversity is associated with significant disturbances of white matter microstructure, particularly in the corpus callosum ( McCarthy-Jones et al, 2018 ). This could therefore account in part for the opposing findings in the corpus callosum observed in these two studies ( Hinton et al, 2019 , Riem et al, 2019 ). Furthermore, the neural correlates of general psychopathology may take a dynamic course over the lifespan, thereby affecting associations observed in different age ranges (see Table 1 ).…”
Section: The Dimensional Approach: Neuroimaging Studies Of General Psmentioning
confidence: 86%
“…A large diffusion imaging study has investigated an association between the p -factor and microstructural integrity throughout the white matter skeleton in young adults ( Hinton et al, 2019 ). While controlling for specific second-order internalising and externalising factors, this study revealed a positive relationship between general psychopathology and FA in the body of the corpus callosum, indicating interhemispheric hyperconnectivity.…”
Section: The Dimensional Approach: Neuroimaging Studies Of General Psmentioning
confidence: 99%
See 1 more Smart Citation